Nanofibrils in nature and materials engineering - Ling, Shengjie; Kaplan, David L.; Buehler, Markus J. (Nature reviews. Materials, 2018)
Nanofibrillar materials, such as cellulose, chitin and silk, are highly ordered architectures, formed through the self-assembly of repetitive building blocks into higher-order structures, which are stabilized by non-covalent interactions. This hierarchical building principle endows many biological materials with remarkable mechanical strength, anisotropy, flexibility and optical properties, such as structural colour. These features make nanofibrillar biopolymers interesting candidates for the development of strong, sustainable and biocompatible materials for environmental, energy, optical and biomedical applications. However, recreating their architecture is challenging from an engineering perspective. Rational design approaches, applying a combination of theoretical and experimental protocols, have enabled the design of biopolymer-based materials through mimicking nature's multiscale assembly approach. In this Review, we summarize hierarchical design strategies of cellulose, silk and chitin, focusing on nanoconfinement, fibrillar orientation and alignment in 2D and 3D structures. These multiscale architectures are discussed in the context of mechanical and optical properties, and different fabrication strategies for the manufacturing of biopolymer nanofibril-based materials are investigated. We highlight the contribution of rational material design strategies to the development of mechanically anisotropic and responsive materials and examine the future of the material-by-design paradigm. Nanofibrils are abundant and critical structural components in nature that can be exploited for novel and sustainable materials. In this Review, hierarchical design strategies for cellulose, silk and chitin nanofibrils in nature and in materials engineering are discussed.